Pembelajaran IPS sebagai Kunci Kecerdasan Sosial Siswa Sekolah Dasar - Nur Haizah Aopmonaim (Journal of Humanities, Social Sciences, and Education, 2025)
Social studies (IPS) education in elementary schools plays a crucial role in developing students' social intelligence. Social intelligence refers to the ability to interact effectively within social contexts, demonstrate empathy, and solve problems in societal settings. This article aims to examine how social studies education can contribute to the development of social intelligence among elementary school students. Through a literature review, this study gathers findings from previous research showing that social studies education not only provides knowledge in areas like geography, history, economics, and society, but also teaches social values, ethics, and communication skills essential for students' lives. Interactive and context-based learning approaches enhance students' abilities to understand various social issues and resolve them. The findings suggest that active learning methods such as group discussions, case studies, and role-playing can strengthen students' social intelligence, allowing them to apply social skills in everyday life. This research also highlights the importance of teachers in facilitating learning that emphasizes collaboration, empathy, and positive attitudes toward social diversity.